They never said it : a book of fake quotes, misquotes, and misleading attributions - Boller, Paul F.; George, John H. (New York : Oxford University Press, 1990)
A reference work that sifts through hundreds of misquotations, wrong attributions, and blatant fabrications to reveal the origins of famous quotes.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Quotations; Errors and blunders, Literary; Literary curiosa; Literary forgeries and mystifications; Quotation; Citations; Erreurs et bévues littéraires.; Curiosités littéraires.; Faux et supercheries littéraires.; Citation; quotations (texts); REFERENCE; Errors and blunders, Literary; Literary curiosa; Literary forgeries and mystifications; Quotation; Quotations; Berühmte Persönlichkeit; Zitat; Irrtum; Quotations